Differences in the frequency of positive and negative emotional experiences in women with different types of eating disorders - Pascual-Jimeno, Aitziber; Apodaca-Urquijo, Pello; Etxebarria-Bilbao, Itziar; Cruz-Sáez, Maria Soledad (Anales de Psicología / Annals of Psychology, 2012)
With the aim of exploring the emotional experience of women suffering from eating disorders (EDs), we analyzed the frequency with which women with different types of EDs have diverse positive and negative emotional experiences. Participants were 98 women with EDs and 100 controls. Of the women with EDs, 17 had purgative bulimia nervosa (BN), 17 had non-purgative BN, 42 fulfilled the majority of DSM-IV-TR criteria for BN and 22 fulfilled the majority of criteria for anorexia nervosa (AN). The Positive and Negative Emotional Experience Frequency Scale was designed ad hoc for the study. The results revealed that women who experienced positive emotions less frequently and negative emotions more frequently were those who fulfilled the majority of criteria for AN. Also, the clearest emotional differences were observed between those who fulfilled the majority of criteria for AN and those who fulfilled the majority of criteria for BN. In addition to having important clinical implications, these results also suggest the need to continue studying this question in order to confirm whether (as the results suggest) it is necessary to review the DSM-IV-TR non-specific disorder category.